MAMACA : The Tradition of Reading Arabic Texts from an Ethnolinguistic-Aesthetic Perspective - Isnaini, Anisah (Fakultas Tarbiyah, 2025)
This study aims to analyze the Mamaca tradition within the context of reading Arabic texts from an ethnolinguistic-aesthetic perspective. The research approach used is literature-based, with content analysis applied for data interpretation. The findings show that the Mamaca tradition, from an ethnolinguistic-aesthetic perspective, functions not only as a ritual of reading Arabic texts but also strengthens the collective identity and religious perception of the community. Through the synergy of text (layang), reader (pamaos), and translator (paneges), Arabic in Mamaca is regarded as sacred, creating a profound spiritual experience while adapting Islamic values to local culture. This tradition merges linguistic beauty with spiritual meaning, enriching the cultural identity of Madura within an Islamic context